On the future contents of a small journal of histochemistry - Pellicciari, C. (PAGEPress Publications, 2012)
In the last three years, more than 70,000 scientific articles have been published in peer reviewed journals on the application of histochemistry in the biomedical field: most of them did not appear in strictly histochemical journals, but in others dealing with cell and molecular biology, medicine or biotechnology. This proves that histochemistry is still an active and innovative discipline with relevance in basic and applied biological research, but also demonstrates that especially the small histochemical journals should likely reconsider their scopes and strategies to preserve their authorship. A review of the last three years volumes of the European Journal of Histochemistry, taken as an example of a long-time established small journal, confirmed that the published articles were widely heterogeneous in their topics and experimental models, as in this journal's tradition. This strongly suggests that a journal of histochemistry should keep its role as a forum open to an audience as broad as possible, publishing papers on cell and tissue biology in a wide variety of models. This will improve knowledge of the basic mechanisms of development and differentiation, while helping to increase the number of potential authors since scientists who generally do not use histochemistry in their research will find hints for the applications of histochemical techniques to novel still unexplored subjects.